2015
DOI: 10.1007/s12663-015-0859-1
|View full text |Cite
|
Sign up to set email alerts
|

An Erupted Silent Tumour

Abstract: Odontomas are the most common odontogenic tumors of the oral cavity which are nonaggressive, hamartomatous in nature consisting of enamel, dentin and cementum. They are called as composite because they contain more than one type of tissue. They are generally asymptomatic, hence recognised on routine radiologic examination. The compound odontoma is composed of multiple small tooth like structures, whereas the complex odontoma consists of a conglomerate mass of enamel and dentine, which bears no anatomical simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…For Kudva et al (2016), odontomas may be seen in different stages of development. In the first stage, radiolucence is shown, due to lack of calcification.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For Kudva et al (2016), odontomas may be seen in different stages of development. In the first stage, radiolucence is shown, due to lack of calcification.…”
Section: Resultsmentioning
confidence: 99%
“…Levi-Duque et al (2019) concluded that 63.3% of the cases were found in routine radiographic exams, 30% due to the lack of permanent tooth eruption, 5% due to infectious symptomatology and only 1.7% as a consequence of increase in volume. Therefore, it is consensual in the literature that in the majority of cases the odontomas are found in complementary exams, such as routine radiographs (KUDVA et al, 2016;MALTAGLIATI et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations